2002
DOI: 10.1074/jbc.m202604200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Collagenase-3 and Osteocalcin Gene Expression by Collagen and Osteopontin in Differentiating MC3T3-E1 Cells

Abstract: Both collagenase-3 and osteocalcin mRNAs are expressed maximally during the later stages of osteoblast differentiation. Here, we demonstrate that collagenase-3 mRNA expression in differentiating MC3T3-E1 cells is dependent upon the presence of ascorbic acid, is inhibited in the presence of the collagen synthesis inhibitor, 3,4-dehydroproline, and is stimulated by growth on collagen in the absence of ascorbic acid. Transient transfection studies show that collagenase-3 promoter activity increases during cell di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 84 publications
2
36
0
1
Order By: Relevance
“…Although Runx2 is critical for the commitment of mesenchymal stem cells into the osteoblast lineage (16,(31)(32)(33), transgenic mice overexpressing Runx2 under the control of the osteoblast-specific Col1a1 promoter exhibit decreased bone mineralization and increased bone resorption (34). Although in the Runx2 osteoblast-overexpressing transgenic mice, the osteoblast number is increased at an early differentiation stage, osteoblast functions (matrix production and mineralization) were impaired in these cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…Although Runx2 is critical for the commitment of mesenchymal stem cells into the osteoblast lineage (16,(31)(32)(33), transgenic mice overexpressing Runx2 under the control of the osteoblast-specific Col1a1 promoter exhibit decreased bone mineralization and increased bone resorption (34). Although in the Runx2 osteoblast-overexpressing transgenic mice, the osteoblast number is increased at an early differentiation stage, osteoblast functions (matrix production and mineralization) were impaired in these cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…For example, bone morphogenetic proteins induce osteoblast differentiation and bone formation through SMADs-Runx2 interactions (19,45). Likewise, PTH increases the expression of rat collagenase 3 in osteoblasts via cooperative interactions between AP-1 and Runx2 (17,18). Our recently published work demonstrates that the OSE1 in the mOG2 promoter is necessary and sufficient for PTH induction of the Ocn gene (35).…”
Section: Fig 4 Atf4 and Runx2 Cooperatively Activate Ocn Transcriptmentioning
confidence: 99%
“…Studies on the collagenase-3 gene promoter showed that both a RUNX2 binding site and a conserved AP-1 binding site are necessary for PTH stimulation (38,39,53,54). Mutations in either site that abrogated the binding of RUNX2 or c-Fos/c-Jun, respectively, abolished PTH stimulation of promoter activity.…”
Section: Fig 5 Effect Of Pth Treatment On the Binding Of Nuclear Exmentioning
confidence: 99%
“…Whether Osf1 is regulated by this mechanism needs to be determined. Finally, PTH may alter interactions between Osf1 and other proteins much as it modifies interactions between RUNX2 and AP-1 factors on the collagenase gene (39,53). Determining the precise mechanisms through which PTH regulates Osf1 transcriptional activity must await the availability of molecular reagents for Osf1.…”
Section: Fig 5 Effect Of Pth Treatment On the Binding Of Nuclear Exmentioning
confidence: 99%
See 1 more Smart Citation